Mário de Andrade: an interrupted text or a finished text? - Lopez, Telê Porto Ancona (Manuscrítica: Revista de Crítica Genética, 1993)
Considering the distinction among unfinished, interrupted and concluded texts in Mário de Andrade’s creative process, in his known unpublished writings, the study concentrates on the writing of Balança, Trombeta e Battleship, a short story that was the object of a genetic edition in 1993.